A hydrogen bond-anchored amide-free fluorinated acrylate-based solid-state electrolyte, and a preparation method and applications thereof

CN121076238BActive Publication Date: 2026-09-15JILIN DONGCHI NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511269275.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-05
Publication Date
2026-09-15
Estimated Expiration
2045-09-05

AI Technical Summary

Technical Problem

然而,酰胺类DES中的游离极性基团会与锂金属负极发生副反应,导致界面不稳定,加速锂枝晶生长和电解质分解,严重限制其在锂金属电池中的应用

Benefits of technology

[0017] This invention provides a method for preparing a hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte, comprising the following steps: mixing lithium salt, fluorinated acrylate, crosslinking agent, amide deep eutectic solvent and thermal initiator, and subjecting the resulting precursor solution to a thermal polymerization reaction to obtain a hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121076238B_ABST
    Figure CN121076238B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of solid electrolytes, and particularly relates to a hydrogen bond anchoring amide free fluorinated acrylate standard solid electrolyte as well as a preparation method and application thereof. Lithium salt, fluorinated acrylate, crosslinking agent, amide deep eutectic solvent and thermal initiator are mixed, and a precursor solution obtained through the mixing is subjected to a thermal polymerization reaction to obtain the hydrogen bond anchoring amide free fluorinated acrylate standard solid electrolyte. The electrolyte can effectively limit the free amide molecules, significantly improve the stability between the electrolyte and the electrode interface, and improve the ionic conductivity, interface stability and safety of a lithium ion battery prepared by using the electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrolyte technology, specifically relating to a hydrogen-bonded amide-anchored fluorinated acrylate reference solid electrolyte, its preparation method, and its application. Background Technology

[0002] In recent years, with the continuous growth in demand for high-energy-density and high-safety batteries from electric vehicles and portable electronic devices, traditional liquid lithium batteries face severe challenges due to safety hazards such as flammability and leakage. Against this backdrop, solid-state lithium batteries, due to their use of solid electrolytes (SPEs), exhibit significant safety advantages and uniform lithium deposition. Among these, polymer solid electrolytes have become a research hotspot due to their excellent flexibility and processing performance. In particular, acrylate polymer electrolytes have attracted considerable attention due to their good film-forming properties and mechanical properties; however, their practical applications are still limited by their relatively low room-temperature ionic conductivity (typically <10). -5 (S / cm) and a narrower electrochemical window.

[0003] To address this critical issue, researchers developed a quasi-solid-state electrolyte (QSSE) system based on acrylates, introducing deep eutectic solvents (DES), particularly amide-based deep eutectic systems. These DESs offer advantages such as high lithium salt solubility, non-flammability, low volatility, and a wide electrochemical window, significantly improving the ionic conductivity of the electrolyte. However, the free polar groups in amide-based DES can undergo side reactions with the lithium metal anode, leading to interfacial instability, accelerated lithium dendrite growth, and electrolyte decomposition, severely limiting their application in lithium metal batteries. Summary of the Invention

[0004] In view of this, the purpose of the present invention is to provide a hydrogen-bonded fluorinated acrylate reference solid electrolyte that anchors amide ionization. This electrolyte can effectively limit the ionization of amide molecules, significantly improve the stability between the electrolyte and the electrode interface, and improve the ionic conductivity, interface stability and safety of lithium-ion batteries prepared therefrom.

[0005] To achieve the above objectives, the present invention provides the following technical solution:

[0006] This invention provides a method for preparing a hydrogen-bonded amide-anchored fluorinated acrylate reference solid electrolyte, comprising the following steps:

[0007] A precursor solution was obtained by mixing lithium salt, fluorinated acrylate, crosslinking agent, amide deep eutectic solvent and thermal initiator, and then subjected to thermal polymerization to obtain a hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte.

[0008] Preferably, the fluorinated acrylate includes one or more of hexafluorobutyl acrylate, hexafluorobutyl methacrylate, and 1,1,1,3,3,3-hexafluoroisopropyl acrylate.

[0009] Preferably, the crosslinking agent comprises polyethylene glycol diacrylate and / or polyethylene glycol dimethacrylate.

[0010] Preferably, the molar ratio of the fluorinated acrylate to the crosslinking agent is 1 to 6:1.

[0011] Preferably, the amide-based deep eutectic solvent includes one or more of N-methylacetamide, N-ethylacetamide, and N-methylpropionamide.

[0012] Preferably, the lithium salt includes one or more of lithium hexafluorophosphate, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium dioxoborate, and lithium difluorooxalateborate.

[0013] Preferably, the molar ratio of amide groups to lithium salt in the amide-based deep eutectic solvent is 2 to 10:1.

[0014] The present invention also provides a hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte prepared by the preparation method described above, comprising a fluorinated acrylate reference solid material and a lithium salt dissolved in the fluorinated acrylate reference solid material; the fluorinated acrylate reference solid material is a thermopolymer of fluorinated acrylate, a crosslinking agent and an amide deep eutectic solvent.

[0015] The present invention also provides the application of the hydrogen-bonded amide-anchored fluorinated acrylate reference solid electrolyte described in the above technical solution in lithium-ion batteries.

[0016] The present invention also provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a barrier medium, and an electrolyte, characterized in that the electrolyte is a hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte as described in the above technical solution.

[0017] This invention provides a method for preparing a hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte, comprising the following steps: mixing lithium salt, fluorinated acrylate, crosslinking agent, amide deep eutectic solvent and thermal initiator, and subjecting the resulting precursor solution to a thermal polymerization reaction to obtain a hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte.

[0018] This invention utilizes a thermal initiator to initiate an in-situ thermal polymerization reaction of fluorinated acrylate, a crosslinking agent, and an amide-based deep eutectic solvent. The strongly electronegative fluorine atoms (F) in the fluorinated acrylate can form an intermolecular hydrogen bond network with the amide groups (NH / C=O), effectively limiting the release of the amide-based deep eutectic solvent and reducing its side reactions with lithium metal, thereby significantly improving the stability between the electrolyte and the electrode interface. In addition, the high bond energy of the CF bond endows the fluorinated acrylate with excellent antioxidant capabilities, which can broaden the high-voltage stability of the electrolyte. At the same time, the hydrophobicity of the fluorinated segments can inhibit water penetration and avoid side reactions. While maintaining the high ionic conductivity advantage of the acrylate-based solid electrolyte, it effectively solves the interfacial stability problem between the amide deep eutectic system and the lithium metal anode, giving it high ionic conductivity and a wide electrochemical window. The lithium-ion battery assembled with it has excellent cycle stability.

[0019] The results of the examples show that the hydrogen-bonded amide-anchored fluorinated acrylate reference solid electrolyte prepared in this invention has an ionic conductivity of 1.96 × 10⁻⁶ at room temperature. -4 With a capacitance of S / cm, it exhibits high ionic conductivity; and in lithium-ion batteries with lithium iron phosphate cathode, it retains 93.86% of its capacity after 270 cycles at 0.5C; and in lithium-ion batteries with NCM811 cathode, it retains 86.81% of its capacity after 200 cycles at 0.2C, demonstrating good cycle stability. Attached Figure Description

[0020] Figure 1 The diagram shows the thermal polymerization process in Example 1, where a is the precursor solution and b is the fluorinated acrylate reference solid electrolyte (PHPE) after thermal polymerization.

[0021] Figure 2 SEM images of the polyethylene membrane and hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte prepared in Example 1, where a is the polyethylene membrane and b is the hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte.

[0022] Figure 3 Impedance spectra of the hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte (PHPE) prepared in Example 1 and the acrylate reference solid electrolyte (PPE) prepared in Comparative Example 1.

[0023] Figure 4 Linear sweep voltammetry curves of the hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte (PHPE) prepared in Example 1 and the acrylate reference solid electrolyte (PPE) prepared in Comparative Example 1.

[0024] Figure 5The graphs show the cycle performance of the lithium-ion battery (PHPE) assembled in Application Example 1 using lithium iron phosphate (LiFeO4) as the positive electrode and fluorinated acrylate-based solid electrolyte, and the lithium-ion battery (PPE) assembled in Comparative Application Example 1 using lithium iron phosphate (LiFeO4) as the positive electrode and acrylate-based solid electrolyte, at 0.5C.

[0025] Figure 6 In application example 1, LiNi 0.8 Co 0.1 Mn 0.1 The cycling performance curves at 0.2C are shown for a lithium-ion battery (PHPE) assembled with O2 (NCM811) as the positive electrode and fluorinated acrylate-based solid electrolyte and a lithium-ion battery (PPE) assembled with NCM811 as the positive electrode and acrylate-based solid electrolyte in Comparative Application Example 1. Detailed Implementation

[0026] This invention provides a method for preparing a hydrogen-bonded amide-anchored fluorinated acrylate reference solid electrolyte, comprising the following steps:

[0027] A precursor solution was obtained by mixing lithium salt, fluorinated acrylate, crosslinking agent, amide deep eutectic solvent and thermal initiator, and then subjected to thermal polymerization to obtain a hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte.

[0028] Unless otherwise specified, the present invention does not have special requirements on the source of raw materials used, and commercially available products well known to those skilled in the art can be used.

[0029] In one embodiment, the fluorinated acrylate includes one or more of hexafluorobutyl acrylate (Formula I-1), hexafluorobutyl methacrylate (Formula I-2), and 1,1,1,3,3,3-hexafluoroisopropyl acrylate (Formula I-3), with hexafluorobutyl acrylate (Formula I-1) or hexafluorobutyl methacrylate (Formula I-2) being used in specific embodiments.

[0030] In this invention, the strongly electronegative fluorine atom (F) in the fluorinated acrylate can form an intermolecular hydrogen bond network with the amide group (NH / C=O). By limiting the types of fluorinated acrylate to the above-mentioned range, it can be ensured that the quasi-solid polymer electrolyte provided by this invention can effectively limit the release of the amide solvent and reduce its side reactions with lithium metal.

[0031]

[0032] In one embodiment, the crosslinking agent includes polyethylene glycol diacrylate (Formula II-1) and / or polyethylene glycol dimethacrylate (Formula II-2), with polyethylene glycol diacrylate (Formula II-1) being a specific example.

[0033] In this invention, the crosslinking agent can crosslink with fluorinated acrylate. By limiting the type of crosslinking agent to the above-mentioned range, the crosslinking reaction can be carried out smoothly, thus ensuring the electrochemical performance of the lithium-ion battery.

[0034]

[0035] In one embodiment, the molar ratio of the fluorinated acrylate to the crosslinking agent is 1 to 6:1; in another embodiment, it is 2 to 5:1; and in a specific embodiment, it is 3 to 4:1.

[0036] By limiting the molar ratio of fluorinated acrylate to the crosslinking agent to the above range, the present invention can control the amount of fluorinated acrylate grafted onto the crosslinking agent.

[0037] In one embodiment, the amide-based deep eutectic solvent includes one or more of N-methylacetamide, N-ethylacetamide, and N-methylpropionamide, with N-methylacetamide being used in a specific embodiment.

[0038] In this invention, amide-based deep eutectic solvents can improve the ionic conductivity of fluorinated acrylate reference solid electrolytes and reduce interfacial impedance. By limiting the types of amide-based deep eutectic solvents to the above-mentioned range, the ability to transport lithium ions can be further improved.

[0039] In one embodiment, the lithium salt includes one or more of lithium hexafluorophosphate, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium dioxoborate, and lithium difluorooxalate borate. In a specific embodiment, it is a mixture of lithium bis(trifluoromethanesulfonyl)imide and lithium difluorooxalate borate. The mass ratio of lithium bis(trifluoromethanesulfonyl)imide to lithium difluorooxalate borate in the mixture is 10:1.

[0040] This invention limits the types of lithium salts to the range described above, which can further improve the conductivity of fluorinated acrylate-based solid polymer electrolytes, thereby improving the performance of lithium-ion batteries.

[0041] In one embodiment, the molar ratio of amide groups to lithium salt in the amide-based deep eutectic solvent is 2 to 10:1, and in a specific embodiment it is 4 to 5:1.

[0042] The present invention limits the types and proportions of lithium salts to the above-mentioned range, which can further improve the electrochemical performance of lithium-ion batteries prepared with electrolytes.

[0043] In one embodiment, the total mass of the fluorinated acrylate and the crosslinking agent is 10-50% of the mass of the hydrogen-bonded anchored amide free fluorinated acrylate reference solid electrolyte; in another embodiment, it is 30-40%; and in a specific embodiment, it is 30%.

[0044] This invention limits the total mass ratio of fluorinated acrylate and crosslinking agent to the above-mentioned range. It can utilize the strong electronegative fluorine atoms (F) in fluorinated acrylate to form an intermolecular hydrogen bond network with amide groups (NH / C=O), effectively limiting the free flow of amide solvent and reducing its side reactions with lithium metal, thereby significantly improving interfacial stability and thus improving the cycle stability of the battery.

[0045] In one embodiment, the thermal initiator includes azobisisobutyronitrile and / or azobisisoheptanenitrile, with azobisisobutyronitrile being used in a specific embodiment; the mass of the thermal initiator is 0.1-1% of the total mass of the lithium salt, fluorinated acrylate, crosslinking agent and amide-based deep eutectic solvent, or 0.3-0.8% in another embodiment, and 0.5% in a specific embodiment.

[0046] In this invention, the polymerization reaction is initiated by a thermal initiator. By limiting the type and content of the thermal initiator to the above-mentioned range, the smooth progress of the thermal polymerization reaction can be ensured.

[0047] In one embodiment, lithium salt, fluorinated acrylate, crosslinking agent, amide-based deep eutectic solvent and thermal initiator are mixed as follows: lithium salt, fluorinated acrylate, crosslinking agent and amide-based deep eutectic solvent are first mixed, and the resulting raw material premix is ​​second mixed with thermal initiator.

[0048] In one embodiment, the first mixing is carried out under stirring conditions; the stirring speed is 100-300 r / min, and in a specific embodiment it is 200-300 r / min; the temperature of the first mixing is room temperature; the time of the first mixing is 5-12 h, and in a specific embodiment it is 8-12 h.

[0049] By limiting the rotation speed, temperature, and time of the first mixing to the ranges mentioned above, the present invention can ensure that the reactants are mixed evenly, which is beneficial to the free radical polymerization reaction during subsequent heating.

[0050] In one embodiment, the second mixing is carried out under stirring conditions; the stirring speed is 100-300 r / min, specifically 200-300 r / min in this embodiment; the temperature of the second mixing is room temperature; and the mixing time is 1-2 h, specifically 1-1.5 h in this embodiment. By limiting the stirring speed, temperature, and time of the second mixing to the above ranges, this invention ensures that the reactants are thoroughly and uniformly mixed, and avoids spontaneous free radical polymerization of the thermal initiator and monomer reagent.

[0051] In one embodiment, the temperature of the thermal polymerization reaction is 60-80°C, specifically 70°C in this embodiment; the time of the thermal polymerization reaction is 1-2 hours, specifically 1.5-2 hours in this embodiment; the thermal polymerization reaction is carried out in a vacuum oven; the vacuum degree of the vacuum oven is -0.8 to -1 MPa, specifically -1 MPa in this embodiment; the specific method of the thermal polymerization reaction is as follows: the precursor solution is spread evenly in a container to carry out the thermal polymerization reaction.

[0052] In this invention, fluorinated acrylate is grafted onto a crosslinking agent during the thermal polymerization reaction to form a crosslinked polymer. By limiting the temperature and time of the thermal polymerization reaction to the above-mentioned range, the thermal polymerization reaction can be fully carried out, thereby improving the performance of the lithium-ion battery prepared from the fluorinated acrylate-based solid polymer electrolyte.

[0053] This invention utilizes a thermal initiator to initiate an in-situ thermal polymerization reaction of fluorinated acrylate, a crosslinking agent, and an amide-based deep eutectic solvent. The highly electronegative fluorine atoms (F) in the fluorinated acrylate can form an intermolecular hydrogen bond network with the amide groups (NH / C=O), effectively limiting the release of the amide solvent and reducing its side reactions with lithium metal, thereby significantly improving interfacial stability. Furthermore, the high bond energy of the CF bonds endows the fluorinated acrylate with excellent antioxidant capabilities, broadening the high-voltage stability of the electrolyte. Simultaneously, the hydrophobicity of the fluorinated segments inhibits water penetration and prevents side reactions. While maintaining the high ionic conductivity advantage of acrylate-based solid electrolytes, this invention effectively solves the interfacial stability problem between the amide deep eutectic system and the lithium metal anode.

[0054] The present invention also provides a hydrogen-bonded anchored amide-free fluorinated acrylate reference solid electrolyte prepared by the preparation method described above, comprising a fluorinated acrylate reference solid material and a lithium salt dissolved in the fluorinated acrylate reference solid material; the fluorinated acrylate reference solid material is a thermopolymer of fluorinated acrylate, a crosslinking agent and an amide deep eutectic solvent.

[0055] In one embodiment, the thickness of the hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte is 18–21 μm, specifically 18.9 μm, 19.3 μm, or 20.1 μm in certain embodiments.

[0056] The present invention also provides the application of the hydrogen-bonded amide-anchored fluorinated acrylate reference solid electrolyte described in the above technical solution in lithium-ion batteries.

[0057] The present invention also provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a barrier medium, and an electrolyte, wherein the electrolyte is a hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte as described in the above technical solution.

[0058] In one implementation, the cathode is LiFeO4 and / or LiNi. 0.8 Co 0.1 Mn 0.1 O2 (NCM811), specifically LiNi in this embodiment. 0.8 Co 0.1 Mn 0.1 O2; the negative electrode is metallic lithium; the barrier medium is a membrane; the membrane includes one or more of polyethylene, polypropylene, cellulose and glass fiber, with polyethylene or polypropylene in a specific embodiment; the thickness of the membrane is 10-100 μm, with 10-50 μm in a specific embodiment.

[0059] As one embodiment, the lithium-ion battery assembly method is as follows: after assembling the positive electrode, the barrier medium and the negative electrode in sequence, the precursor solution is injected to completely wet the barrier medium, and then a thermal polymerization reaction is carried out to obtain the lithium-ion battery.

[0060] The present invention does not have a special limitation on the volume of the injected precursor solution; it can be selected conventionally according to the volume of the lithium-ion battery.

[0061] In one embodiment, the injection volume of the precursor solution is 20–50 μL, and in a specific embodiment it is 35 μL.

[0062] In one embodiment, the lithium-ion battery is assembled in an argon-filled glove box; the contents of H2O and O2 in the argon-filled glove box are independently ≤0.1ppm.

[0063] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention, but they should not be construed as limiting the scope of protection of the present invention.

[0064] Example 1

[0065] The preparation method of hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte is as follows:

[0066] (1) Lithium bis(trifluoromethanesulfonyl)imide, hexafluorobutyl acrylate (Formula I-1), polyethylene glycol diacrylate (Formula II-1), and N-methylacetamide were stirred at 300 r / min for 12 h to obtain a raw material premix; the molar ratio of hexafluorobutyl acrylate (Formula I-1) to polyethylene glycol diacrylate (Formula II-1) was 3:1; the molar ratio of N-methylacetamide to lithium bis(trifluoromethanesulfonyl)imide was 4:1; and the total mass of the fluorinated acrylate and crosslinking agent was 30% of the mass of this quasi-solid electrolyte.

[0067] (2) The raw material premix obtained in step (1) is stirred with azobisisobutyronitrile at a speed of 300 r / min for 1 h to obtain a precursor solution; the mass of the azobisisobutyronitrile is 0.5% of the mass of the raw material premix.

[0068] (3) The precursor solution obtained in step (2) is heated in a vacuum oven at 70°C and a vacuum degree of -1MPa for 1.5h to initiate a thermal polymerization reaction by a thermal initiator to obtain a hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte (hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte membrane); the thickness of the hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte membrane is 19.3μm.

[0069] Example 2

[0070] The difference from Example 1 is that hexafluorobutyl acrylate (Formula I-1) is replaced with hexafluorobutyl methacrylate (Formula I-2), otherwise it is the same as Example 1.

[0071] Example 3

[0072] The difference from Example 1 is that polyethylene glycol diacrylate (Formula II-1) is replaced with polyethylene glycol dimethacrylate (Formula II-2), otherwise the same as Example 1.

[0073] Comparative Example 1

[0074] The difference from Example 1 is that only polyethylene glycol diacrylate is used as the polymer monomer to prepare the acrylate-based polymer quasi-solid electrolyte. The preparation method of the acrylate-based solid electrolyte is as follows:

[0075] (1) Lithium bis(trifluoromethanesulfonyl)imide, polyethylene glycol diacrylate (Formula II-1) and N-methylacetamide were stirred at 300 r / min for 12 h to obtain a raw material premix; the molar ratio of N-methylacetamide to lithium bis(trifluoromethanesulfonyl)imide was 4:1; the total mass of the crosslinking agent was 30% of the mass of this quasi-solid electrolyte;

[0076] (2) The raw material premix obtained in step (1) is stirred with azobisisobutyronitrile at a speed of 300 r / min for 1 h to obtain a precursor solution; the mass of the azobisisobutyronitrile is 0.5% of the mass of the raw material premix.

[0077] (3) The precursor solution obtained in step (2) is heated in a vacuum oven at 70°C and a vacuum degree of -1MPa for 1.5h to initiate a thermal polymerization reaction by a thermal initiator to obtain an acrylate-based solid electrolyte (acrylate-based solid electrolyte membrane).

[0078] Application Examples 1-3

[0079] Batteries were assembled in an argon-filled glove box (H2O and O2 contents ≤0.1ppm), using LiFeO4 and LiNi respectively. 0.8 Co 0.1 Mn 0.1 Using O2 as the positive electrode, lithium metal as the negative electrode, and a 17μm thick polyethylene membrane as the barrier medium, 35μL of the precursor solutions obtained in Examples 1 to 3 are injected into each cell to fully impregnate the barrier medium. The cells are then placed in a vacuum oven at 70°C and a vacuum degree of -1MPa and heated for 1.5h to carry out a thermal polymerization reaction, thereby obtaining a lithium-ion battery.

[0080] Comparative Application Example 1

[0081] The difference from Application Example 1 is that the precursor solution prepared in Example 1 is replaced with the precursor solution prepared in Comparative Example 1.

[0082] Performance testing

[0083] The microstructure of the polyethylene diaphragm and the hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte (hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte membrane) before and after thermal polymerization was observed using scanning electron microscopy.

[0084] The impedance of hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte (hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte membrane) was tested by room temperature constant voltage EIS using a Princeton P4000 electrochemical workstation. The test frequency range was 1MHz to 1Hz.

[0085] The electrochemical window of the hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte (hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte membrane) was tested by linear sweep voltammetry, with a test voltage range of 0 to 6 V.

[0086] The charge-discharge process and cycle stability of lithium-ion batteries were tested using the LAND CT2001A test system at room temperature and at voltages of 2.5–3.8V and 2.8–4.3V.

[0087] The thermal polymerization process in Example 1 is as follows: Figure 1 As shown, a is the precursor solution, and b is the polymerized fluorinated acrylate reference solid electrolyte. From Figure 1 As can be seen, the thermal polymerization reaction is complete, and there is no flowing liquid.

[0088] SEM images of the polyethylene membrane and the hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte (hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte membrane) prepared in Example 1 are shown below. Figure 2As shown, a is a polyethylene diaphragm, and b is a hydrogen-bonded amide-anchored fluorinated acrylate reference solid electrolyte. From Figure 2 It can be seen that the white, opaque appearance and rich porous structure of the polyethylene membrane facilitate the full penetration of the precursor solution. After curing, the electrolyte uniformly fills the pores of the polyethylene membrane, making the membrane change from opaque to translucent. At the same time, the porous structure disappears, forming a smooth and defect-free surface, ensuring close contact between the electrolyte and the electrode material.

[0089] The impedance spectra of the hydrogen-bonded amide-anchored fluorinated acrylate reference solid electrolyte (PHPE) prepared in Example 1 and the acrylate reference solid electrolyte (PPE) prepared in Comparative Example 1 are shown below. Figure 3 As shown. By Figure 3 It can be seen that the resistance R of the electrolyte is 5.02 Ω for PHPE electrolyte and 8.06 Ω for PPE electrolyte. The thicknesses of the PHPE and PPE electrolyte films are 19.3 μm and 18.6 μm, respectively. According to Formula 1, the room temperature ionic conductivity of the fluorinated acrylate quasi-solid polymer electrolyte PHPE provided by this invention is calculated to be 1.96 × 10⁻⁶. -4 S / cm, while the room temperature ionic conductivity of the acrylate-based solid electrolyte PPE in Comparative Example 1 was 1.18 × 10⁻⁶. -4 S / cm, where σ is the ionic conductivity (S / cm), l is the thickness of the solid polymer electrolyte membrane (cm), R is the resistance of the electrolyte (Ω), and S is the effective area of ​​the solid polymer electrolyte (cm²). 2 By comparing the ionic conductivity of Example 1 and Comparative Example 1, it is evident that the introduction of fluorinated acrylate significantly improves the ionic conductivity of the electrolyte and substantially enhances its ion transport capacity.

[0090]

[0091] The linear sweep voltammetric curves of the hydrogen-bonded amide-anchored fluorinated acrylate reference solid electrolyte (PHPE) prepared in Example 1 and the acrylate reference solid electrolyte (PPE) prepared in Comparative Example 1 are shown below. Figure 4 As shown, from Figure 4 As can be seen, the oxidation potential of the PHPE electrolyte membrane reaches 4.8V, while that of the PPE electrolyte membrane is only 4.3V, indicating that the introduction of fluorinated acrylate broadens the electrochemical window and has high oxidation stability.

[0092] Application Example 1 uses lithium iron phosphate (LiFeO4) as the positive electrode and fluorinated acrylate quasi-solid electrolyte to assemble a lithium-ion battery (PHPE). The cycle performance curves at 0.5C for the lithium-ion battery (PPE) assembled in Comparative Application Example 1 using lithium iron phosphate (LiFeO4) as the positive electrode and acrylate reference solid electrolyte are shown below. Figure 5 ,from Figure 5 As can be seen, after 270 cycles at 0.5C, the discharge specific capacity of the PHPE lithium-ion battery after the first cycle is 155 mAh / g, and after 270 cycles it is 150 mAh / g, with a capacity retention of 93.86%. In contrast, after 120 cycles at 0.5C, the discharge specific capacity of the PPE lithium-ion battery after the first cycle is 144 mAh / g, and after 120 cycles it is 121 mAh / g, with a capacity retention of only 80.67%. Comparing the cycle performance of Application Example 1 and Comparative Application Example 1 clearly shows that PHPE has a longer cycle count and a higher capacity retention, indicating that lithium-ion batteries made with hydrogen-bonded amide-based fluorinated acrylate reference solid electrolytes have good cycle stability.

[0093] Application Example 1 uses LiNi 0.8 Co 0.1 Mn 0.1 The cycle performance curves at 0.2C for a lithium-ion battery (PHPE) assembled with O2 (NCM811) as the positive electrode and fluorinated acrylate-based solid electrolyte and a lithium-ion battery (PPE) assembled with NCM811 as the positive electrode and acrylate-based solid electrolyte in Comparative Application Example 1 are shown below. Figure 6 As shown, from Figure 6 As can be seen, after 200 cycles at 0.2C, the discharge specific capacity of the PHPE lithium-ion battery after the first cycle is 200 mAh / g, and after 200 cycles it is 174 mAh / g, with a capacity retention rate of 86.81%. In contrast, after 157 cycles at 0.2C, the discharge specific capacity of the PPE lithium-ion battery after the first cycle is 133 mAh / g, and after 157 cycles it is only 102 mAh / g, with a capacity retention rate of 76.6%. Comparing the discharge specific capacity and capacity retention rate in Application Example 1 and Comparative Application Example 1 clearly shows that PHPE performs superiorly, indicating that lithium-ion batteries made with hydrogen-bonded amide-anchored fluorinated acrylate reference solid electrolytes have the advantage of high voltage resistance.

[0094] Table 1 shows the room temperature ionic conductivity test data of the hydrogen-bonded amide-anchored fluorinated acrylate reference solid electrolytes in Examples 1-3.

[0095] Table 1. Room temperature ionic conductivity test data of hydrogen-bonded amide-free fluorinated acrylate reference solid electrolytes in Examples 1-3.

[0096] 1 19.3 <![CDATA[1.96×10 -4 ]]> 2 20.1 <![CDATA[0.87×10 -4 ]]> 3 18.9 <![CDATA[2.33×10 -4 ]]>

[0097] Table 2 shows the first-cycle discharge specific capacity and capacity retention rate after 270 cycles at 0.5C for lithium-ion batteries assembled using lithium iron phosphate (LiFeO4) as the positive electrode and fluorinated acrylate quasi-solid electrolyte in Application Examples 1-3.

[0098] Table 2 shows the first-cycle discharge specific capacity and capacity retention of lithium-ion batteries using LiFeO4 as the positive electrode in Application Examples 1-3.

[0099] Application Example 1 155 93.86 Application Example 2 150 85.43 Application Example 3 152 89.87

[0100] Application Examples 1-3: LiNi 0.8 Co 0.1 Mn 0.1 Table 3 shows the first-cycle discharge specific capacity and capacity retention rate of lithium-ion batteries assembled using O2 (NCM811) as the positive electrode and fluorinated acrylate quasi-solid electrolyte.

[0101] Table 3 shows the first-cycle discharge specific capacity and capacity retention of lithium-ion batteries using NCM811 as the positive electrode in Application Examples 1-3.

[0102] Application Example 1 200 86.81 Application Example 2 180 85.44 Application Example 3 195 79.81

[0103] As can be seen from Tables 1-3, the hydrogen-bonded amide-anchored fluorinated acrylate reference solid electrolyte provided in Example 1 of this invention has an ionic conductivity of 1.96 × 10⁻⁶ at room temperature. -4 With a capacitance of S / cm, it exhibits high ionic conductivity; and in lithium-ion batteries with lithium iron phosphate cathode, it retains 93.86% of its capacity after 270 cycles at 0.5C; in lithium-ion batteries with NCM811 cathode, it retains 86.81% of its capacity after 0.2C cycling, demonstrating good cycle stability.

[0104] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a hydrogen-bonded amide-anchored fluorinated acrylate reference solid electrolyte, characterized in that, Includes the following steps: A precursor solution was mixed with lithium salt, fluorinated acrylate, crosslinking agent, amide deep eutectic solvent and thermal initiator, and then subjected to thermal polymerization to obtain hydrogen bond anchored amide free fluorinated acrylate reference solid electrolyte. The fluorinated acrylates include one or more of hexafluorobutyl acrylate, hexafluorobutyl methacrylate, and 1,1,1,3,3,3-hexafluoroisopropyl acrylate. The crosslinking agent includes polyethylene glycol diacrylate and / or polyethylene glycol dimethacrylate; The amide-based deep eutectic solvent includes one or more of N-methylacetamide, N-ethylacetamide, and N-methylpropionamide.

2. The preparation method according to claim 1, characterized in that, The molar ratio of the fluorinated acrylate to the crosslinking agent is 1~6:

1.

3. The preparation method according to claim 1, characterized in that, The lithium salt includes one or more of lithium hexafluorophosphate, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium dioxoborate, and lithium difluorooxalateborate.

4. The preparation method according to claim 1 or 3, characterized in that, The molar ratio of amide groups to lithium salt in the amide-based deep eutectic solvent is 2~10:

1.

5. The hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte prepared by the preparation method according to any one of claims 1 to 4, characterized in that, It includes a fluorinated acrylate reference solid material and a lithium salt dissolved in the fluorinated acrylate reference solid material; the fluorinated acrylate reference solid material is a thermopolymer of fluorinated acrylate, a crosslinking agent and an amide-based deep eutectic solvent.

6. The application of the hydrogen-bonded amide-free fluorinated acrylate reference solid electrolyte of claim 5 in lithium-ion batteries.

7. A lithium-ion battery, comprising a positive electrode, a negative electrode, a barrier medium, and an electrolyte, characterized in that, The electrolyte is the hydrogen-bonded, amide-anchored, fluorinated acrylate reference solid electrolyte as described in claim 5.

Citation Information

Patent Citations

  • Gel polymer electrolyte and preparation method and application thereof

    CN119230930A